COMPARISON OF AGE ESTIMATES FROM VARIOUS HARD PARTS FOR REDFIN PERCH, Percafluviatilis, IN TASMANIA - Irwan Jatmiko; James Haddy; Mike Williams (Indonesian Fisheries Research Journal, 2013)
Whole otoliths, sectioned otoliths, scales and vertebrae were used to select the most suitable for age determination of redfin perch, Percafluviatilis. Redfin perch were sampled from Trevallyn Lake and Brushy Lagoon using fyke nets, gillnets, electrofishing and rod and line angling. Age estimates were assessed for comparison between readings and among structures. One-wayANOVA of readability scores highlighted that sectioned otolith was the most obvious compare to other hard parts. Sectioned otoliths also showed the highest (93.9%) agreement between readings, followed by vertebrae (68.7), scales (38.8) and whole otoliths (29.9). Furthermore, there were no significantly different (p>0.05) between first and second readings from sectioned otolith and vertebrae but significantly different (p <0.05) to those from scales and whole otoliths. When sectioned otoliths’ ages were compared with other structures, vertebrae showed the highest (47.6%) agreement to those followed by scales (25.2%) and whole otoliths (20.4%). Age estimates from sectioned otoliths were significantly different (p<0.05) to the values obtained from vertebrae, scales and whole otoliths.This finding demonstrated that sectioned otoliths are the best hard part for age determination for redfin perch in Tasmania.